Human epidermal growth factor receptor-2 gene expression positivity determined by silver in situ hybridization/immunohistochemistry methods and associated factors in a cohort of Sri Lankan patients with gastric adenocarcinoma: a prospective study. Issue 2 (February 2023) - Subasinghe, Duminda; Acott, Nathan; Mahesh, Pasyodun Koralage Buddhika; Sivaganesh, Sivasuriya; Munasinghe, Sithum; Kumarasinghe, Mariyan Priyanthi; Samarasekera, Dharmabandu Nandaveva; Lokuhetty, Menaka Dilani Samarawickrema
Objective: Positive human epidermal growth factor 2 (HER2) expression and its predictive clinicopathological features remain unclear in Sri Lankan gastric cancer (GC) patients. Here, we aimed to determine GC HER2 status predictors by analyzing associations between clinicopathological features and HER2 expression using immunohistochemistry (IHC) and silver in situ hybridization (SISH). Methods: During this 4-year prospective study, clinicopathological data were collected from participants in the National Hospital of Sri Lanka. HER2 IHC and SISH were performed using commercial reagents. Using chi-square tests, associations of HER2-IHC/SISH with clinicopathological features were analyzed. Results: Overall, 145 GC patients were included, 69 had gastrectomies and 76 had biopsies. Positive HER2 expression by IHC was associated with age <60 years, high T stage (assessed pathologically in resections and radiologically in biopsies), high nuclear grade, tumor necrosis, mitosis >5/high-power field, with additional perineural invasion and lymphovascular invasion in resections. These features, excluding lymphovascular invasion but including male sex, were associated with HER2 expression by SISH. Conclusions: Age <60 years, high nuclear grade, tumor necrosis, and perineural invasion are associated factors of HER2 status. These could be used to triage GC patients for HER2 status testing in limited resource settings where IHC/SISH analysis is costly.